2019
DOI: 10.3310/hta23300
|View full text |Cite
|
Sign up to set email alerts
|

Tumour profiling tests to guide adjuvant chemotherapy decisions in early breast cancer: a systematic review and economic analysis

Abstract: Background Breast cancer and its treatment can have an impact on health-related quality of life and survival. Tumour profiling tests aim to identify whether or not women need chemotherapy owing to their risk of relapse. Objectives To conduct a systematic review of the effectiveness and cost-effectiveness of the tumour profiling tests oncotype DX® (Genomic Health, Inc., Redwood City, CA, USA), MammaPrint® (Agendia, Inc., Amste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 450 publications
(860 reference statements)
2
44
0
1
Order By: Relevance
“…Unfortunately, we were unable to deduce the details of the ASCO evidence rating approach and also the criteria and judgments that were used to determine the strength of the recommendations. Unlike us, ASCO and NICE made recommendations on the 12-MS and the PAM50-RORS to guide treatment decisions, 55 , 62 mainly because they did not exclude studies based on prognostic results only.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we were unable to deduce the details of the ASCO evidence rating approach and also the criteria and judgments that were used to determine the strength of the recommendations. Unlike us, ASCO and NICE made recommendations on the 12-MS and the PAM50-RORS to guide treatment decisions, 55 , 62 mainly because they did not exclude studies based on prognostic results only.…”
Section: Discussionmentioning
confidence: 99%
“…A costeffectiveness study conducted by the UK National Institute for Excellence in Health and Care found that neither ODX nor MMP are cost effective from the perspective of the UK health system. 39 No predictive role of the bene t of chemotherapy was considered for ODX or MMP. Notably, at the time of performing this analysis, the results of the TAILORx trial were unknown, which demonstrated the ability of ODX to establish the bene t of adjuvant chemotherapy and not only its ability to establish prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The Prosigna assay (based on the PAM50 signature) measures 58 genes (50 cancer-related genes and eight controls) and classifies a patient’s tumour into a subtype based on the signature (luminal A, luminal B, HER-2 enriched or basal-like) [ 46 ]. The test is designed for postmenopausal women with early, ER-positive, HER2-negative breast cancer with up to three positive lymph nodes, receiving 5 years of hormonal therapy [ 14 ].…”
Section: Tumour-based Toolsmentioning
confidence: 99%